2011 IEEE 27th International Conference on Data Engineering 2011
DOI: 10.1109/icde.2011.5767908
|View full text |Cite
|
Sign up to set email alerts
|

A novel probabilistic pruning approach to speed up similarity queries in uncertain databases

Abstract: In this paper, we propose a novel, effective and efficient probabilistic pruning criterion for probabilistic similarity queries on uncertain data. Our approach supports a general uncertainty model using continuous probabilistic density functions to describe the (possibly correlated) uncertain attributes of objects. In a nutshell, the problem to be solved is to compute the PDF of the random variable denoted by the probabilistic domination count: Given an uncertain database object B, an uncertain reference objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The idea is to derive for each database object O, a lower and an upper bound of the probability that O has a higher score than Q. Using these approximations, we can apply the concept of uncertain generating functions [19] in order to obtain an (initial) approximated result of a PIR query, which guarantees that the true result is bounded correctly. The problem at hand is to update these uncertain generating functions efficiently when an update is fetched from the stream.…”
Section: Discussionmentioning
confidence: 99%
“…The idea is to derive for each database object O, a lower and an upper bound of the probability that O has a higher score than Q. Using these approximations, we can apply the concept of uncertain generating functions [19] in order to obtain an (initial) approximated result of a PIR query, which guarantees that the true result is bounded correctly. The problem at hand is to update these uncertain generating functions efficiently when an update is fetched from the stream.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in [5], the computational complexity is linear in k, yielding a total of O(|DB| 2 × k) for the probabilistic pruning. Verification: The verification step can be performed analogously to the k = 1 case using the algorithm proposed in [6], which has been designed for k ≥ 1.…”
Section: Probabilistic Rknn Queriesmentioning
confidence: 99%
“…In the first experiment (cf. Figure 6(a)), we varied the parameter k. It can be observed that the runtime scales slightly worse than linearly, which can be explained by the usage of uncertain generating functions that show a complexity of O(k 2 ) ( [5]). This is notable, since naive approaches need to consider all N k possible results.…”
Section: Cpu-costmentioning
confidence: 99%
See 1 more Smart Citation
“…Since expensive integration operations are involved in this step, a number of efficient methods have been proposed. In [11], [36], efficient methods were proposed to generate answer objects' probability bounds without performing expensive integration operations.…”
Section: • Formentioning
confidence: 99%